2009
DOI: 10.1007/s12529-009-9034-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Stress Reactivity and Recovery of Novelty Seekers

Abstract: The findings suggest that high novelty seekers may be more stress resilient because they might have faster cardiac recovery after stress. Cardiac stress reactivity seems not to be among the explaining factors for the association between novelty seeking and coronary heart disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Indeed there is a growing body of evidence that temperament influences the way one perceives environmental stimuli [10], and mentally [11] and physiologically [4] responds to them. The role of temperament in stress vulnerability has been demonstrated in experimental studies [4,11,12]. Furthermore, the significance of temperament in association with health problems has been reported in cross-sectional research [7] as well as in prospective epidemiological data [13].…”
Section: Introductionmentioning
confidence: 96%
“…Indeed there is a growing body of evidence that temperament influences the way one perceives environmental stimuli [10], and mentally [11] and physiologically [4] responds to them. The role of temperament in stress vulnerability has been demonstrated in experimental studies [4,11,12]. Furthermore, the significance of temperament in association with health problems has been reported in cross-sectional research [7] as well as in prospective epidemiological data [13].…”
Section: Introductionmentioning
confidence: 96%
“…Temperament traits are assumed to constitute antecedent conditions that influence subsequent conditions, and therefore, can be considered as moderators of all stress phenomena [15]. Temperament characteristics may predispose individuals to react differently in stressful encounters [7,10,11,16,17]. In arousaloriented theories of temperament (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that in women smaller FMD was associated with higher anger-in, and in men smaller FMD tended to be associated with higher hostility. Next, Hintsanen, Puttonen, Järvinen, Pulkki-Råback, Elovainio, Merjonen, and Keltikangas-Järvinen [6] focus on sympathetic and parasympathetic laboratory-induced stress reactivity and recovery in healthy young adults, and test if the cardiac stress reactivity and recovery explain the previous findings linking novelty-seeking temperament with increased risk factor levels of cardiovascular disease. The authors found no support for their hypothesis as high-novelty seekers did not differ from low-novelty seekers in stress reactivity, and recovered faster from stress.…”
mentioning
confidence: 97%